Perspectives of essential oils usage in dermatological medicines - Kiseliova, Kateryna; Vyshnevska, Liliia (Annals of Mechnikov’s Institute, 2023)
Aim of work. Theoretical substantiation of the effectiveness of essential oils’ use as APIs in medicinal preparations for the treatment of dermatological diseases. Materials and methods. In the course of the research, data from scientific literary sources was analyzed and the following methods were used: experimental and theoretical, generalization, analysis of statistical data. Results and discussion. Analysis of scientific studies of the antibacterial activity of essential oils has shown the effectiveness of using essential oils of cinnamon, clove, eucalyptus, tea tree, lavender, and basil for acne therapy, which are effective against the microorganisms that cause acne. Essential oils have a wide potential for use in the therapy of dermatological diseases (mycoses, seborrheic dermatitis, pyoderma,candidiasis) and small superficial wounds. Experimental studies have shown the presence of antibacterial, antifungal, anti-inflammatory of essential oils. The analysis of scientific resources showed the use of essential oils for the treatment of diseases of the respiratory tract, digestive system, nervous system, gynecological, andrological, endocrine and cardiovascular pathologies. The analysis of medicinal products on the pharmaceutical market of Ukraine showed that essential oils are used mainly as auxiliary substances and as APIs in the composition of drugs with expectorant, antibacterial, hypnotic and sedative effects. Conclusions. Generalization of the analysis of scientific literature demonstrated the wide possibilities of using essential oils in the therapy of acne, mycoses, seborrheic dermatitis, and superficial wounds. The analysis of the composition of drugs on the pharmaceutical market of Ukraine showed that essential oils are used to a limited extent as APIs, which indicates the relevance of pharmaceutical development of drugs with different directions of action, and primarily dermatological drugs with essential oils. Key words: essential oils, dermatology, dermatological medicines